A qualitative systematic review on the experiences of self-management in community-dwelling older women living with chronic illnesses - Tay, Z.; Poon, W.; Hegney, Desley (University of Adelaide, 2011)
Background: With the risk of chronic conditions increasing with age, older women are likely to have co-morbid chronic conditions. In addition, they may have to contend with socioeconomic issues unique to their gender which can challenge their self-management. Objective: The aim of the systematic review was to determine the best available evidence related to the experiences of self-management among community-dwelling older women with chronic conditions, specifically non-communicable illnesses which include cardiovascular disease, chronic respiratory diseases, diabetes mellitus and arthritis. Inclusion criteria: Types of participants included all older women with the following characteristics: aged sixty-five years and above; living in their own community dwellings; community setting rural, suburban or urban; living alone or with others; having co-morbidities and having chronic illnesses for a minimum of one year. Phenomenon of interest was experiences of self-management among community-dwelling older women with chronic conditions. Interpretive studies were considered in the review, which included but were not limited to designs like phenomenology, grounded theory, action research, feminist research and ethnography. Search strategy: The search strategy aimed to uncover both published and unpublished studies, in English language only, and was unrestricted by time. The databases searched included CINAHL, MEDLINE, PsycINFO (Ovid), Scopus, Embase, Science Direct, Sociological Abstracts, Social Sciences Citation Index (Web of Science), Proquest and Google Scholar. Preliminary keywords were drawn from the topic of the systematic review.Methodological quality: Each paper was assessed independently by two reviewers for methodological quality. The Joanna Briggs Institute Qualitative Assessment and Review Instrument QARI Critical Appraisal Checklist for Interpretive & Critical Research was used to appraise the methodological quality of all papers. Data collection: Qualitative data were extracted from papers included in the review using standardized data extraction tools developed by the Joanna Briggs Institute. Data synthesis: Qualitative research findings were synthesized using the Joanna Briggs Institute-Qualitative Assessment and Review Instrument. Results: 88 findings from six studies were aggregated into 22 categories, and then into five synthesized findings. The five synthesized findings are: (i) losing control over a failing body, (ii) maintaining control, (iii) developing self-expertise, (iv) re-defining health, and (v) relying on social support.Conclusions: For these women, self-management involves reclaiming and maintaining their sense of control over their bodies, which is constantly threatened by their chronic illnesses. In addition, they redefine their meaning of health in the context of illness to maintain their emotional well-being in spite of their illness. Implications for practice: Healthcare providers can assist their older female patients in maintaining their sense of control through effective symptom management and practical strategies to manage daily life. Because social support is crucial to self-management by older women, healthcare providers should include, where relevant, family members and other loved ones in patient education. Healthcare providers should also endeavour to build and maintain a positive relationship with their patients through effective communication as the provider-patient relationship is a strong influence on an older woman’s experience in self-management. Implications for research: Further research is warranted in older women of other cultural backgrounds as the majority of reviewed studies focused on Caucasians in the United States.